Efecto del sustrato suelo en la germinación y crecimiento de Eucalyptus globulus labill hasta los 60 días en condiciones de laboratorio. - Martell Fernandez, Yenyfer (2016)
The research is conducted in laboratory conditions using material obtained in the open, in order to determine the substrate soil provides higher rate of germination and growth of Eucalyptus globulus Labill, considering evaluate the time of seed germination, variation in growth in the seedling and germination percentage in each type of substrate, which was used as a material substrate types soil cultivated, uncultivated, a channel of the river, garden, with its combinations, and seeds of Eucalyptus globulus Labill that they arranged in a randomized experimental design; thus the results of population estimates were obtained, germination rate, no significant difference between types of soil substrate with parts of the seedling and while the significant difference between soil types; so it is concluded that the cultivated soil combined with soil yard drive greater growth potential of stem, seeds of Eucalyptus globulus Labill have a chance to germinate and grow in any soil and combinations thereof, and the seeds of "eucalyptus" they have higher germination rate in cultivated soil. Keywords: germination, growth, soil substrate, Eucalyptus globulus Labill.